Aerobic Exercise and Healthy Nutrition as Neuroprotective Agents for Brain Health in Patients with Parkinson's Disease: A Critical Review of the Literature - Davide Maria Cammisuli; Ubaldo Bonuccelli; Simona Daniele; Claudia Martini; Jonathan Fusi; Ferdinando Franzoni (MDPI AG, 2020)
Parkinson's disease (PD) is characterized by motor and nonmotor features that have an influence on patients' quality of life at different levels. To date, some evidences have arisen on the effectiveness of physical trainings and nutrients intake in ameliorating functional and cognitive outcomes in PD patients. Physical activity is effective in improving both motor and nonmotor features and recent epidemiological investigations have revealed the pivotal role that dietary patterns may play in reducing the risk of PD highlighting the pathogenesis of the neurodegeneration. Specifically, aerobic exercise shows beneficial effects in improving motor functions and executive control in PD patients, as well as proper nutrition may help in improving neuroprotective agents counteracting neurodegeneration and allows patients to better interact with the medication. Our narrative review critically focused on aerobic exercise and nutrition in PD in order to point out the best prescriptions for brain health of affected patients. Implications for a therapeutic plan and rehabilitation for these patients are also discussed.